Developing a chronic kidney disease clinic in primary care - Watcharananan, Yingluk; Pongsittisak, Wanjak (Journal of the Nephrology Society of Thailand, 2022)
Chronic kidney disease (CKD) is a major problem of healthcare systems in Thailand. Diabetes and hypertension have become the most common causes of renal replacement therapy in CKD showing continuously increasing trends. The problem affects general public health, society and economics of the country. Therefore, a good screening system is needed to identify people at risk of CKD, and help prevent and delay progression of CKD before the end stage of kidney failure. Moreover, it could control the severity of complications especially potential heart and vascular diseases. Accordingly, this study aimed to develop a chronic kidney disease clinic in primary care. The objectives were to improve service quality and accessibility. The emphasis focused on developing personnel in primary health care and multidisciplinary disciplines. A one stop service network was created at the community level involving a network of partners operating in the community. The patient-centered care, was delivered using physician’s internal medicine under the supervision of a nephrologist involved to monitor the treatment process in the same direction. Information monitoring systems for patients with chronic kidney were developed to link effectively between the hospital and community care efforts. The results could achieve the goal of reducing or delaying CKD progression as well as complications in both risk and disease groups. Moreover, the CKD clinic in primary care was cost-effective and efficiently reduced mortality long term for patients with chronic kidney. disease.